Filling gaps in the biology of the endemic and threatened freshwater shrimp Macrobrachium candango (Caridea: Palaemonidae) through basic morphometric and reproductive approaches - Nogueira, Caio Santos [UNESP]; Mossolin, Emerson Contreira; Ribeiro, Mauro César Lambert Brito; Mantelatto, Fernando Luis (Sociedade Brasileira de Carcinologia, 2022)
Macrobrachium candango Mantelatto, Pileggi, Pantaleão, Magalhães, Villalobos and Álvarez, 2021 is an endemic shrimp species to the Brazilian Central-West region (Brasília, Federal District). The present study aims to analyze the relative growth, morphometry, morphological sexual maturity, and fecundity of this species. Specimens were collected from tributaries of the Paranoá Lake hydrographic basin, Brasília, during sporadic periods between 1983 and 2012. Relative growth was analyzed for different structures (carapace, abdomen, second abdominal pleura, merus, carpus, and propodus). The laterality and heterochely patterns were evaluated based on the dimensions of the propodus length. Fecundity was calculated as the average total number of eggs per female and egg size was measured to obtain the volume. There were differences in relative growth (p < 0.05) of the structures analyzed between juveniles and adults, and distinct allometric patterns were observed between the life stages, which could reflect the habit of these animals at each developmental stage. No pattern of laterality and heterochely was observed between the chelipeds of the animals analyzed (p > 0.05). The lack of laterality may indicate that this species directs energy to the smallest propodus when the largest propodus is injured. Egg volume ranged from 4.41 to 7.71 mm3, and fecundity ranged from 38 to 61 eggs, indicating a life cycle with abbreviated larval development. The characteristics presented herein are unprecedented for M. candango and present relevant information needed to assess the conservation status of this species, which is currently threatened.
Keywords: Conservation; fecundity; heterochely; laterality; relative growth